2021
DOI: 10.1097/jcn.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support for Implantable Cardioverter-Defibrillator Replacement

Abstract: Background Decision support can help patients facing implantable cardioverter-defibrillator (ICD) replacement understand their options and reach an informed decision reflective of their preferences. Objective The aim of this study was to evaluate the feasibility of a decision support intervention for patients faced with the decision to replace their ICD. Methods A pilot feasibility randomized trial was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The included trials were modest in size with the exception of Hess et al 8 and Kunneman et al ,9 reporting on 898 and 922 patients, respectively. Trials were conducted exclusively in high-income countries, including the USA (Allen et al ,10 Case et al ,11 Coylewright et al ,12 Doll et al ,13 Fraenkel et al ,14 Hess et al ,15 Hess et al ,8 Kostick et al ,16 Kunneman et al 9 and Thomas et al 17), UK (Thomson et al 18) and Canada (Carroll et al ,19 Holbrook et al ,20 Lewis et al ,21 Man-Son-Hing et al ,22 McAlister et al ,23 Morgan et al 24 and Schwalm et al 25). No trials were conducted in low-income or middle-income countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included trials were modest in size with the exception of Hess et al 8 and Kunneman et al ,9 reporting on 898 and 922 patients, respectively. Trials were conducted exclusively in high-income countries, including the USA (Allen et al ,10 Case et al ,11 Coylewright et al ,12 Doll et al ,13 Fraenkel et al ,14 Hess et al ,15 Hess et al ,8 Kostick et al ,16 Kunneman et al 9 and Thomas et al 17), UK (Thomson et al 18) and Canada (Carroll et al ,19 Holbrook et al ,20 Lewis et al ,21 Man-Son-Hing et al ,22 McAlister et al ,23 Morgan et al 24 and Schwalm et al 25). No trials were conducted in low-income or middle-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…A broad range of clinical conditions in cardiology were covered, including atrial fibrillation and anticoagulation (Fraenkel et al ,14 Hoolbrook et al ,20 Kunneman et al ,9 Man-Son-Hing et al ,22 McAlister et al 23 and Thomson et al 18), chest pain and coronary artery disease (Case et al ,11 Coylewright et al ,12 Doll et al ,13 Hess et al ,15 Hess 8 et al and Morgan et al 24), cardiac devices and pacemakers (Carroll et al ,19 Lewis et al 21 and Thomas et al 17), as well as advanced treatment options, including left ventricular assist devices (Allen et al 10 and Kostick et al 16). Included trials used a variety of formats in patient decision aids to improve SDM, including printed aids (Allen et al ,10 Carroll et al ,19 Coylewright et al ,12 Hess et al ,15 Hess et al ,8 Holbrook et al ,20 Kostick et al ,16 Lewis et al ,21 McAlister et al ,23 Man-Son-Hing et al ,22 Morgan et al 24 and Schwalm et al 25), audiotapes (Holbrook et al ,20 McAlister et al 23 and Man-Son-Hing et al 22), video (Allen et al ,10 Morgan et al 24 and Thomas et al 17), coaching (Lewis et al 21) and online/computer programs (Case et al ,11 Doll et al ,13 Fraenkel et al ,14 Holbrook et al ,20 Kunneman et al 9 and Thomson et al 18). Details of reviewers’ structured assessment of methodological quality of included studies6 are shown in table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Strengthening the nurses' role to incorporate interventions facilitating shared decision-making such as decision coaching would equally empower affected women and nurses. Single studies have demonstrated the effectiveness and feasibility of nurses delivering such interventions [28,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Learning more about their disease in a structured learning situation depends on a substantial level of patient cognition and unbiased education. PDAs are intended to assure that balanced information is presented, and some studies use scales to evaluate the SDM process objectively [ 10 , 11 ]. Giving patient access to unbiased information rather than controlling what the patient knows reflects a commitment to sharing; but exactly how the information influences patient treatment choice is largely unknown.…”
mentioning
confidence: 99%